Pertumbuhan Bibit Kelapa Sawit(Elaeis guenensis Jacq) Terhadap Pemberian Pupuk Organik Regen® Berbasis Rumput Laut Pada Media Tanam Ultisol di Pembibitan Awal - Nasamsir, Nasamsir; Nengsih, Yulistiati; Pangestu, Niko (Jurnal Media Pertanian, 2024)
Ultisol soil is generally found in the A horizon with low organic matter content and can basically still be used as a planting medium. The aim of the research was to determine the effect of providing seaweed-based Regen organic fertilizer on the growth of oil palm seedlings on Ultisol planting media in early nurseries. Research Rt, 07. Andilan Village, Kasang District, Karang City, Kumpeh Ulu District, Muara Jambi Regency, Jambi Province. Starting from February to April 2024. The design used was a completely randomized design (CRD) with regen fertilizer concentration treatment, includes; p0: without regen organic fertilizer (control), p1: providing regen organic fertilizer 1.5 cc/L + 3 kg planting medium, p2: providing regen organic fertilizer 2.5 cc/L + 3 kg planting media, p3: providing regen organic fertilizer 3.5 cc/L + 3 kg planting medium. The parameters tested were plant height (cm), seedling stem diameter (mm), shoot dry weight (g), root dry weight (g), root shoot ratio, total leaf area (cm2), and soil analysis. Data were analyzed statistically using Anova with a significance level of 5%. If the difference is significant, the test continues with the Duncan/DNMRT 5% test. The results of the research showed that the application of seaweed-based Regen® organic fertilizer had a significant effect on stem diameter but had no significant effect on plant height, crown dry weight, root dry weight, root crown ratio and total leaf area. The conclusion is that giving regen organic fertilizer at a concentration of 3.5 cc/L of water on 3 kg of planting media, in general, has not been able to increase the growth of oil palm seedlings at the age of 12 WAP.Keywords: nursery, oil palm, ultisol, seaweed regen